Investigating Gut Permeability in Animal Models of Disease - González-González, Marianela; Díaz-Zepeda, Camilo; Eyzaguirre-Velásquez, Johana; González-Arancibia, Camila; Bravo, Javier A.; Julio-Pieper, Marcela (Frontiers in Physiology, 2019)
A growing number of investigations report the association between gut permeability and intestinal or extra-intestinal disorders under the basis that translocation of gut luminal contents could affect tissue function, either directly or indirectly. Still, in many cases it is unknown whether disruption of the gut barrier is a causative agent or a consequence of these conditions. Adequate experimental models are therefore required to further understand the pathophysiology of health disorders associated to gut barrier disruption and to develop and test pharmacological treatments. Here, we review the current animal models that display enhanced intestinal permeability, and discuss 1) their suitability to address mechanistic questions, such as the association between gut barrier alterations and disease and 2) their validity to test potential treatments for pathologies that are characterized by enhanced intestinal permeability.